Hubungan anemia dengan kualitas hidup pasien penyakit ginjal kronik yang sedang menjalani hemodialisis reguler - Senduk, Cindy R.; Palar, Stella; Rotty, Linda W. A. (e-CliniC, 2016)
Abstract: The objective of this study is to determine the correlation between anemia and quality of life in chronic kidney disease patients undergoing regular hemodialysis. This was an observational analytical study with a cross-sectional design. Samples were obtained by using consecutive sampling. Patientsâ€™ quality of life was assessed with short-form 36 questionnaires (SF-36) while their Hb levels data were taken from the medical records. There were 60 samples, with a majority age range of 50-59 years old (33.33%) adn the dominant gender was males (68,3%). There were 13 non-anemia patients (22%), 27 mild anemia patients (45.0%), 15 moderate anemia patients (25.0%) and 5 severe anemia patients (8%). The highest quality of life score obtained was 90.70 with an average score 61.99. The Spearman correlation test showed a correlation between anemia and life quality (p=0.000). Conclusion: There was a significant correlation between anemia and quality of life in chronic kidney disease patients undergoing regular hemodialysis.Keywords: chronic kidney disease, hemodialysis, anemia, quality of lifeÂ Abstrak: Tujuan dari penelitian ini untuk mengetahui hubungan anemia dengan kualitas hidup pasien PGK yang sedang menjalani hemodialisis reguler. Desain penelitian yang digunakan adalah analitik observasional dengan rancangan studi potong silang (cross sectional study). Teknik pengambilan sampel yang digunakan yaitu consecutive sampling. Data kualitas hidup pasien diukur dengan pertanyaan dalam kuesioner Short Form (SF-36) sedangkan kadar Hb diambil dari rekam medik. Hasil dari penelitian ini didapatkan sampel 60 orang, usia terbanyak 50-59 tahun (33,3%), jenis kelamin terbanyak adalah laki-laki (68,3%), tidak anemia 13 orang (22%), anemia ringan 27 orang (45,0%), 15 orang (25,0%) anemia sedang dan sisanya 5 orang (8%) anemia berat. Skor kualitas hidup tertinggi 90,70 dengan rata-rata 61,99. Uji korelasi spearman didapatkan hubungan antara anemia dengan kualitas hidup (p=0,000). Simpulan: Terdapat hubungan yang signifikan antara anemia dengan kualitas hidup pasien PGK yang sedang menjalani hemodialisis reguler.Kata kunci: penyakit ginjal kronik, hemodialisis, anemia, kualitas hidup